A rare case of periprosthetic supracondylar fracture with fracture medial condyle of femur after total knee arthroplasty - Palit, Sukanya (International Journal of Research in Orthopaedics, 2022)
Periprosthetic supracondylar fracture with fracture of medial condyle of femur after total knee arthroplasty (TKA), is of rare incidence. The risk factors include morbid obesity, increased varus deformity after primary TKA, osteopenia, prolonged use of corticosteroids or even trivial trauma leading to stress fractures. We reported a case of periprosthetic supracondylar fracture with fracture medial condyle of right femur after TKA in a patient of rheumatoid arthritis, with severe varus right knee and morbid obesity. X rays of knee revealed the periprosthetic supracondylar fracture with anterior femoral notching; CT scans revealed supracondylar fracture with severe comminuted fracture of right prosthetic medial condyle. Revision arthroplasty was done with augmented long-stem implant and patient was discharged on the 10th post-operative day. Knee movement at 6 months was 0-120 degrees with satisfactory outcome scores on follow-up. Periprosthetic supracondylar fracture with fracture medial condyle of the femoral implant requires immediate diagnosis and treatment; revision arthroplasty is mandatory if associated with morbid obesity, osteopenia and varus knees, after primary TKA. Obesity leads to excessive joint overloading, which together with varus malalignment and poor bone stock, may lead to component loosening, requiring revision arthroplasty. Weight reduction is necessary before primary TKA to improve the functional outcomes and reduce the incidence of revision arthroplasty.